Ethical Issues in Bereavement Research with Minors: A Scoping Review - Athena E. S. Park; Karolina Krysinska; Karl Andriessen (MDPI AG, 2022)
There are various ethical issues in bereavement research. Most of the literature focuses on ethical issues involving adult participants. However, it is conceivable that research with minors poses particular ethical challenges, and little is known of the ethical issues involved in bereavement research with minors. A scoping review adhering to the PRISMA-ScR guidelines was conducted to address this gap and to contribute to better research practices. Searches in Embase, Emcare, EBM Reviews, Medline, PsycINFO (all accessed via Ovid), CINAHL, Scopus, SSCI, and the journals Death Studies and OMEGA identified 40 relevant peer-reviewed articles, while 25 relevant theses/dissertations were identified through ProQuest Global. The main ethical concerns identified include informed consent, risk to participants, and privacy and confidentiality. Findings of this review may inform bereavement researchers when designing their studies and to ensure the safety of their participants. The findings can also be used in clarifying the decisions made to a research ethics board, thus contributing to the quality of the research in this field. Future reviews may examine how the ethical issues reported in this review are similar or different to those reported in research with minors in other fields and expand to include more experimental research.